Influence of steel vacuuming on the reduction of hydrogen content. (January 2020) - Radu, M; Serban, S; Popa, E; Heput, T
Abstract: Under the current technological development, steel consumers are increasingly demanding high quality steels, one of the conditions imposed is the content of gases (hydrogen and nitrogen). At the world level in the technological process of steel production, there are provided facilities for the processing of liquid steel in ladle, at least of type LF-ladle furnace and VD- vacuum degassing. In the researches and experiments carried out the possibilities of the advanced reduction of the hydrogen content, respectively the increase of the elimination level, were considered. As a factor of influence on the aforementioned parameters were chosen: the total duration of the vacuum, the duration of deep vacuum, the vacuum pressure, the inlet-outlet temperatures in the vacuum degassing installation and the distributor. The data obtained were processed in the EXCEL and MATLAB, and on the basis of the technological analysis of the obtained results the optimal limits of variation of the technological parameters were set in order to achieve the aim pursued.